Biokimia Mycobacterium Tuberculosis yang Diberi Perlakuan Obat Anti TB Isoniazid - Elly Karlina; Widodo Widodo; Devi Etivia Purlinda (Poltekkes Kemenkes Semarang, 2019)
Mycobacterium tuberculosis exposed to Isoniazid experienced drug resistance due to morphological and selection factors, with Isoniazid concentrations of 0.5 μg / ml with a contact time of 24 hours, 48 hours, 72 hours, 96 hours, the results obtained in testing for NaCl 5% Kruskal wallis obtained sig 0.005 results there is a treatment effect on growth While in the semi-quantitative catalase test, a sig value of 0.007 was obtained with p 0.01 so it can be concluded that there is a significant influence between the duration of isoniazid exposure. resistance occurs due to the selection of strains that are resistant to treatment during the therapy process at 96 hours exposure with a percentage of 2%. In the exposure process it can be concluded that it will change the resistance to 5% NaCl, changes in Catalase test results and also causes strain selection that is resistant to isoniazid 0.5 µg / ml.